Characterization of health issues in young first‐time blood donors. Issue 3 (5th December 2020) - Hughes, Jonathan A.; Bravo, Marjorie D.; Townsend, Mary; Kamel, Hany
Abstract: Background and objectives: Blood donors, especially young donors, are considered a healthy segment of the population. We sought to identify medical issues that may warrant medical referral in young first‐time blood donors. Materials and methods: A retrospective cohort study was performed in first‐time donors ages 16–22 who presented in a system of nineteen regional United States blood centres over 10 years. Donor health attributes characterized include body mass index, blood pressure, total cholesterol and pre‐donation haemoglobin. Using standardized definitions, overweight and obese body mass, hypertension, elevated cholesterol and anaemia were identified and characterized in this donor population. Results: Among 825 041 young first‐time donors presenting between January 2009 and December 2018, with available measurements, 46·9% were either overweight or obese, 59·8% demonstrated high blood pressure (22·2% elevated blood pressure, 37·6% stage 1 or 2 hypertension), elevated cholesterol was identified among 6·3% of males and 8·8% of females, and anaemia was present in 3·5% of males and 5·2% of females. During the study period, all unfavourable health outcomes significantly increased in prevalence ( P  < 0·0001) when comparing 2009 vs. 2018 rates. Conclusion: Elevated weight and obesity are common in young first‐time allogeneic United States blood donors, with fewer donors having elevated total cholesterol or anaemia. Such medical issues may have significant importance for future health and well‐being as well as continued donor eligibility. Blood centres may be able to help support the identification and mitigation of important medical issues in donors and provide a public health benefit.